Cone-beam computed tomography texture analysis can help differentiate odontogenic and non-odontogenic maxillary sinusitis - Costa, Andre Luiz Ferreira; Fardim, Karolina Aparecida Castilho [UNESP]; Ribeiro, Isabela Teixeira [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Braz-Silva, Paulo Henrique; Orhan, Kaan; de Castro Lopes, Sérgio Lúcio Pereira [UNESP] (XMLink, 2023)
Purpose: This study aimed to assess texture analysis (TA) of cone-beam computed tomography (CBCT) images as a quantitative tool for the differential diagnosis of odontogenic and non-odontogenic maxillary sinusitis (OS and NOS, respectively). Materials and Methods: CBCT images of 40 patients diagnosed with OS (N=20) and NOS (N=20) were evaluated. The gray level co-occurrence (GLCM) matrix parameters, and gray level run length matrix texture (GLRLM) parameters were extracted using manually placed regions of interest on lesion images. Seven texture parameters were calculated using GLCM and 4 parameters using GLRLM. The Mann-Whitney test was used for comparisons between the groups, and the Levene test was performed to confirm the homogeneity of variance (α=5%). Results: The results showed statistically significant differences (P<0.05) between the OS and NOS patients regarding 3 TA parameters. NOS patients presented higher values for contrast, while OS patients presented higher values for correlation and inverse difference moment. Greater textural homogeneity was observed in the OS patients than in the NOS patients, with statistically significant differences in standard deviations between the groups for correlation, sum of squares, sum of entropy, and entropy. Conclusion: TA enabled quantitative differentiation between OS and NOS on CBCT images by using the parameters of contrast, correlation, and inverse difference moment.
Keywords: Computer-Assisted; Cone-Beam Computed Tomography; Diagnosis; Diagnostic Imaging; Paranasal Sinuses